A Comparison of Different Schemes of Neoadjuvant Chemotherapy Followed by Concurrent Chemotherapy and Radiotherapy for Locally Advanced Cervical Cancer: A Retrospective Study - Tian X (Dove Medical Press, 2021)
Xue Tian,1,* Feiyue Yang,2,* Fenghu Li,1 Li Ran,1 Jianying Chang,1 Jiehui Li,1 Wei Hong,3 Lang Shan,1 Yanjun Du,1 Lili Hu,1 Fan Mei,1 Mingyuan He,1 Yongxia Li,1 Heran Wang,1 Kai Zuo,1 Bo Zhou,4 Shuying Chen,1 Wanli Mao1 1Department of Oncology, The Affiliated Hospital of Guizhou Medical University, The Affiliated Cancer Hospital of Guizhou Medical University, Guiyang, 550004, People’s Republic of China; 2Department of Gynecologic Oncology, Guizhou Provincial People’s Hospital, Guiyang, 550004, People’s Republic of China; 3Department of Radiotherapy, The Affiliated Hospital of Guizhou Medical University, The Affiliated Cancer Hospital of Guizhou Medical University, Guiyang, 550004, People’s Republic of China; 4Surgical Department of Gynecological Oncology, The Affiliated Hospital of Guizhou Medical University, The Affiliated Cancer Hospital of Guizhou Medical University, Guiyang, 550004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fenghu Li; Li Ran Email 769654418@qq.com; ranli171@hotmail.comPurpose: To examine the clinical significance of unoperated cervical cancer patients treated with different neoadjuvant chemotherapy (NACT) schemes followed by concurrent chemotherapy and radiotherapy (CCRT).Methods: This retrospective analysis included women with locally advanced cervical cancer treated with NACT-CCRT between September 2011 and September 2014. Neoadjuvant chemotherapy included paclitaxel plus cisplatin (TP group; 62 patients) or paclitaxel plus loplatin (TL group; 58 patients), which were administered three weekly, and cisplatin or loplatin, which were administered weekly for synchronous chemotherapy. External beam radiation therapy (50.4– 56.35 Gy/28 f, 180– 215 cGy/f, 5 f/w) was followed by intracavitary brachytherapy (5 Gy per fraction, mostly 5 fractions, Ir192 based).Results: One hundred twenty women were included in the analysis. The complete/partial response rate was 99.2% after treatment. The one-year, three-year, and five-year survival rates were 99.2%, 82.5%, and 70.8%, respectively. In the TP and TL groups, the three-year and five-year survival rates were 85.5% vs 77.6% and 75.8% vs 65.5%, respectively, with no significant difference. The 5-year overall survival (OS) rates between patients with stage IIB and stage IIIB disease were not significantly different (69.2% vs 64.7%). In the TP group, grade 3 or 4 digestive reactions were more frequent than those in the TL group. Leukopenia, neutropenia, and thrombocytopenia were more common in the TL group. No significant difference was found in anemia, radiation enteritis, radiation proctitis, or radiation cystitis between the groups.Conclusion: Lobaplatin may be used as an alternative drug for patients with severe digestive system reactions or contraindications to cisplatin, but hematological toxicity must be considered, particularly in dose-intensive schemes. Neoadjuvant chemotherapy followed by concurrent chemotherapy and radiotherapy (NACT-CCRT) warrants further prospective study in cervical cancer patients with a wide range of tumor invasion (eg, mass size ≥ 5 cm or stage IIIB).Keywords: cervical cancer, neoadjuvant chemotherapy, survival benefit, side effects